Fontes de ácidos graxos insaturados na alimentação de vacas leiteiras no período seco - Bettero, Vitor Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to evaluate the effects of sources of unsaturated fatty acids to dairy cows in the dry period on the ruminal dynamic and biohydrogenation and intestinal flow of fatty acids. Eight Holstein dry cows cannulated in the rumen and abomasum (614 ± 59 kg of body weight; mean ± SD), were assigned randomly in two contemporary and balanced 4 x 4 Latin squares, fed the following diets: 1) control (C) diet based on corn and soybean meal; 2) refined soybean oil (SO) with addition of 3.0% on total DM 3) Whole soybean raw (WS), with the inclusion of 16.0% on total DM; and 4) calcium salts of unsaturated fatty acids (CS), with the inclusion of 3.2% on total DM. The DM, OM, CP, NDF and TDN intakes did not differ (P> 0.05) between treatments. Diets with fat sources had higher intake of EE (0.72 vs 0.30 kg/day) and lower intake of NFC (3.91 vs 4.40 kg/day) when compared to control. The digestibilities of DM, OM and NDF were higher (P <0.05) in treatment C compared to treatments with lipid addition. In relation to EE, the digestibility of C diet was lower than in other treatments (84.88% vs 86.93%). The concentration of NH3-N was higher (P <0.05) in animals fed C diet than the diets with lipids inclusion (20.39 vs. 17.49 mg/dL). The C diet had the lowest propionate concentration in relation to lipid sources. The SO diet had higher propionate concentrations (P <0.05) compared to WS and CS diets. The acetate: propionate ratio (C2/C3) was higher (P <0.05) in the control diet (4.13) than the diets with supplementation (3.81). The microbial protein synthesis and energy and nitrogen balances were not affected by diets. Animals fed diets with fat supplements had higher total cholesterol and HDL cholesterol in the blood (P <0.05). The SO diet had lower ruminal digestion rates (P <0.05) for DM, NDF and pdNDF compared to WS and CS. WS diet had lower passage rates of DM, NDF and pdNDF (P <0.05) in relation to CS diet ...

O objetivo do trabalho foi avaliar os efeitos de fontes de ácidos graxos insaturados para vacas leiteiras no período seco sobre a dinâmica e bio-hidrogenação ruminais e fluxo intestinal de ácidos graxos. Foram utilizadas 8 vacas secas da raça Holandesa, canuladas no rúmen e abomaso (614 ± 59 kg de peso corporal; média ± dp), agrupadas em dois quadrados latinos 4 x 4 contemporâneos e balanceados, alimentadas com as seguintes dietas: 1) controle (C), dieta a base de milho e farelo de soja; 2) óleo de soja refinado (OS) com inclusão de 3,0% na MS total; 3) Grão de soja cru e integral (GS), com inclusão de 16,0% na MS total; e 4) Sais de cálcio de ácidos graxos insaturados (SC), com inclusão de 3,2% na MS total. Os consumos de MS, MO, PB, FDN e NDT não diferiram (P>0,05) entre tratamentos. Dietas com fontes lipídicas tiveram maior consumo de EE (0,72 vs 0,30 kg/dia) e menor consumo de CNF (3,91 vs 4,40 kg/dia) quando comparadas ao controle. As digestibilidades da MS, MO E FDN foram maiores (P<0,05) no tratamento controle em relação aos tratamentos com adição lipídica. Já em relação ao EE, a digestibilidade da dieta C foi menor (P<0,001) que nos demais tratamentos (84,88% vs 86,93%) . A concentração de N-NH3 foi maior (P<0,05) para os animais que receberam a dieta C em relação às dietas com inclusão de lipídios (20,39 vs 17,49 mg/dL). A dieta C apresentou as menores concentrações de propionato (P=0,001) em relação às fontes lipídicas. Já a dieta OS apresentou maiores concentrações de propionato (P<0,05) em relação às dietas GS e SC. A relação acetato:propionato (C2/C3) foi maior (P<0,05) na dieta controle (4,13) do que nas dietas com suplementação (3,81). A síntese de proteína microbiana e os balanços de energia e nitrogênio não foram influenciados pelas dietas experimentais. Animais que receberam dietas com suplementação lipídica apresentaram maiores valores de colesterol total e ...
Keywords: Bovino de leite - Nutrição; Gordura; Acidos graxos; Digestão; Rúmen; Animal nutrition